Analysis of the Potential Integration of Palm Oil-Cattle in Bireuen Regency, Aceh Province - Nur, TM; Fadli, Chairul; Satriawan, Halus (Universitas Muhammadiyah Yogyakarta, 2018)
The efforts to increase livestock population can be reach by cattle-palm oil integration. Bireuen Regency contributes 13.32% to the population of cattle in Aceh province. The potency of palm oil plantations, and distribution of cattle population is an opportunity to implement the system of integration of cattle-oil palm- in Bireuen Regency.Â The aims of this research were to analyze the potential of system of integration cattle- palm oil - in Bireuen Regency, and to determine the priority of development area of cattle-palm oil- integration. Several analysis that was conducted were: potential analysis of oil palm plantations using Location Quotient, Shift Share Analysis, financial analysis; analysis of level of preference of respondent to farmer group using likert scale; Multiple Criteria Decision MakingÂ with TOPSIS and Analytical Hierarchy Process model. The results shows that Bireuen Regency has considerable potential in developing a system of integration of cattle-palm oil -. This is indicated by R / C ratio 1, LQ 1, positive value of SSA and livestock farming profits between 7-10 million / year, and farmers group preference has a high percentage of positive response on farmer group as a forum for human resource development, cooperation , and increased production. Priority for the development of palm oil-cattle integration system in Bireuen Regency are in Peusangan Siblah Krueng, Peusangan Selatan, Juli and Makmur Subdistrict.